2019
DOI: 10.1186/s12934-019-1194-x
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR–Cas9-mediated genomic multiloci integration in Pichia pastoris

Abstract: Background Pichia pastoris (syn. Komagataella phaffii ) is a widely used generally recognized as safe host for heterologous expression of proteins in both industry and academia. Recently, it has been shown to be a potentially good chassis host for the production of high-value pharmaceuticals and chemicals. Nevertheless, limited availability of selective markers and low efficiency of homologous recombination make this process difficult and time-consuming, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 51 publications
1
85
0
Order By: Relevance
“…Only a few bioprocesses focus on chromosomal genes and most still use plasmids for gene regulation, which are less stable, requires antibiotics and bear a higher metabolic burden (Furubayashi et al., 2015). Several strategies have been employed to solve these problems, such as novel marker-free genetic integration tools based on the CRISPR-Cas system (Klompe et al., 2019; Liu et al., 2019), stable gene expression systems based on an incoherent feedforward loop (iFFL) (Segall-Shapiro et al., 2018) and antibiotic-free plasmids based on Stable and TunAble PLasmid (STAPL) system that encode for translation initiation factors required by a corresponding auxotroph (Kang et al., 2018). Second, most enzymes of carotenoid biosynthesis are from plants and have a low catalytic efficiency in microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few bioprocesses focus on chromosomal genes and most still use plasmids for gene regulation, which are less stable, requires antibiotics and bear a higher metabolic burden (Furubayashi et al., 2015). Several strategies have been employed to solve these problems, such as novel marker-free genetic integration tools based on the CRISPR-Cas system (Klompe et al., 2019; Liu et al., 2019), stable gene expression systems based on an incoherent feedforward loop (iFFL) (Segall-Shapiro et al., 2018) and antibiotic-free plasmids based on Stable and TunAble PLasmid (STAPL) system that encode for translation initiation factors required by a corresponding auxotroph (Kang et al., 2018). Second, most enzymes of carotenoid biosynthesis are from plants and have a low catalytic efficiency in microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…This BiP-driven multiplexed CRISPR/Cas9 system demonstrated successful multiloci integration where multiple gene cassettes simultaneously integrated into Pichia pastoris genome (Fig. 1C) (Liu et al 2019). Use of the constitutive rice BiP1 (OsBiP1) promoter was shown to achieve 86-93% editing efficiencies with tRNA or Csy4 gRNA processing system in rice (Fig.…”
Section: Expression Of Cas Nuclease and Grnas Using Bidirectional Promentioning
confidence: 97%
“…In addition to TCTU and STU CRISPR/Cas expression systems, bidirectional promoters (BiPs) have been recently developed to drive Cas9 and gRNA expression in opposite direction in methylotrophic yeast and rice (Liu et al 2019;Ren et al 2019). P HTX1 , a bidirectional Pol II promoter, was designed to co-regulate the expression of Cas9 and gRNAs flanked by HH and HDV ribozymes with different terminators (Liu et al 2019). This BiP-driven multiplexed CRISPR/Cas9 system demonstrated successful multiloci integration where multiple gene cassettes simultaneously integrated into Pichia pastoris genome (Fig.…”
Section: Expression Of Cas Nuclease and Grnas Using Bidirectional Promentioning
confidence: 99%
“…CRISPR-Cas9 was also used to develop a one-step multiloci gene integration method without the requirement of selective markers. This method can be used for pathway assembly of complicated pharmaceuticals expressed in P. pastoris (Liu Q. et al, 2019). The key factors that can enhance recombinant protein production in P. pastoris were well-described recently, and it was reported that up to 120 g DCW per liter of culture can be achieved using a chemically defined medium (García-Ortega et al, 2019).…”
Section: Yeastmentioning
confidence: 99%